A combined face, fingerprint authentication system - Ali, A.S.O. (Institute of Electrical and Electronics Engineers Inc., 2014)
This work presents a multimodal biometrics system that combines face and fingerprint authentication modules. The proposed face verification module incorporates Gabor Wavelet texture features and face edge features. As for the fingerprint module, a simple algorithm is employed for extracting fingers' Minutia in order to build feature vector for each sample fingerprint. The proposed system can be used effectively for personal identification at international airports checkpoints. Â© 2014 IEEE.